Study of Economic Waste Exchange in Batam City - Yuvita Dian Siswanti; Wahyono Hadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
The problem of industrial waste in Batam City has not been fully solved. For this reason, this study was conducted to examine the concept of the application of the waste exchange and the applications. The waste exchange aims to help industries, especially for manufacturing industry, to solve their waste by opening business opportunities for waste users. It also help related agencies to monitoring and manifesting waste. It can be used as the initiator of joint office to oversee the possibility of transactions and waste traffic, so the waste does not cause impact on the environment. This research was carried out using in-depth interview techniques and consultations. Determining respondents is done by using purposive sampling, which is the respondents are determining by certain considerations. The AHP method used to carry out factors that influence of the waste exchange formation and strategic recommendations to the relevant agency of establishing waste exchange in Batam City. The results of the AHP analysis of the main factors that were prioritized by agency respondents were economic factors (32.4%) and the factors that had the lowest priority were organizational governance (17.1%). Respondents to waste utilization or waste users, technology availability factors have a high priority (43.1%) and the characteristics of waste characteristics have the lowest priority (20%)